Effect of Storage Time and Temperature on Gyrinops walla Gaertn. Seed Germination - De Alwis, H.N.; Subasinghe, S.M.C.U.P.; Hettiarachchi, D.S. (My University, 2016)
Certain members of Aquilaria, Gyrinops, Gonystylus and Aetoxylon genera of Thymelaeaceae family produce a highly valuable resin called agarwood inside the stem, branches and roots. Agarwood is extensively used for manufacturing perfume, incense sticks, traditional medicine and cultural and religious activities in many countries, especially in Asian and Middle East regions. Gyrinops walla is the only agarwood producing species naturally growing in Sri Lanka which can commonly be found in the low country wet zone. Although agarwood producing ability of G. walla was scientifically discovered in 2012, the information available about this species is limited when compared to its closely related species of Aquilaria origin. Due to the high demand of agarwood, G. walla is important to the economy of Sri Lanka and therefore plantation establishment using this species is expected by many sectors. Since large quantities of seedlings are required for plantation establishment, it is essential to discover the successful nursery practices. Therefore the present study was aimed at identifying the germination pattern and potential of storage of G. walla seeds at selected temperature levels. Fresh and healthy seeds of G. walla were collected from the trees growing in homegardens of Mathugama Divisional Secretariat Division. Three temperature levels were selected to store the seeds before sowing in the nursery beds, which resulted 18 different combinations of treatments and 50 seeds were used for each treatment. The selected temperatures for seed storage were room temperature, 80 C and -100 C and the storage time varied from 1 to 6 weeks. Stored seeds were sown at weekly intervals and direct sowing was done without storing as the control. Germination of the seeds were determined at weekly interval for 16 weeks by counting the seedlings. Percentage of germination was calculated and General Linear Model was used to determine the effect of storage temperature, storage period and their interaction on seed germination. In accordance with the results, most of G. walla seeds started germination within 1 to 2 weeks after sowing. Control showed the highest germination percentage (73.3%). The second highest germination percentage (26.7%) showed by the seeds stored at 80 C for 2 and 4 weeks. Seeds stored for 6 weeks at 80 C showed the third highest germination (16.7%). Further analysis revealed significant differences in storage temperatures and time. The results confirmed that G. walla seeds are sensitive to the desiccation and therefore cannot be stored for a long period.
Keywords: Agarwood; Gyrinops walla; Nursery practices; Seed germination; Thymelaeaceae